Aliased Flow Signal Planimetry by Cardiovascular Magnetic Resonance Imaging for Grading Aortic Stenosis Severity: A Prospective Pilot Study - Mantini, Cesare; Khanji, Mohammed Y.; D'Ugo, Emilia; Olivieri, Marzia; Caputi, Cristiano Giovanni; Bufano, Gabriella; Mastrodicasa, Domenico; Calvo Garcia, Darien; Rotondo, Domenico; Candeloro, Matteo; Tana, Claudio; Cademartiri, Filippo; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives Transthoracic echocardiography (TTE) is the standard technique for assessing aortic stenosis (AS), with effective orifice area (EOA) recommended for grading severity. EOA is operator-dependent, influenced by a number of pitfalls, and requires multiple measurements introducing independent and random sources of error. We tested the diagnostic accuracy and precision of aliased orifice area planimetry (AOAcmr), a new, simple, non-invasive technique for grading of AS severity by low-VENC phase-contrast cardiovascular magnetic resonance (CMR) imaging. Methods Twenty-two consecutive patients with mild, moderate or severe AS and 6 age- and sex-matched healthy controls had TTE and CMR examinations on the same day. We performed analysis of agreement and correlation among (i) AOAcmr; (ii) geometric orifice area (GOAcmr) by direct CMR planimetry; (iii) EOAecho by TTE-continuity equation; and (iv) the ‘gold standard’ multimodality EOA (EOAhybrid) obtained by substituting CMR LVOT area into Doppler continuity equation. Results There was excellent pairwise positive linear correlation among AOAcmr, EOAhybrid, GOAcmr and EOAecho (P<0.001); AOAcmr had the highest correlation with EOAhybrid (R2=0.985, P<0.001). There was good agreement between methods, with the lowest bias (0.019) for the comparison between AOAcmr and EOAhybrid. AOAcmr yielded excellent intra- and inter-rater reliability (intraclass correlation coefficient: 0.997 and 0.998, respectively). Conclusions Aliased orifice area planimetry by 2D phase-contrast imaging is a simple, reproducible, accurate ‘one-stop shop’ CMR method for grading AS, potentially useful when echocardiographic severity assessment is inconclusive or discordant. Larger studies are warranted to confirm and validate these promising preliminary results.